Metabolic disruption of gold nanospheres, nanostars and nanorods in human metastatic prostate cancer cells - Soares, Sílvia (2023)
Nanomaterials offer a broad spectrum of applications in biomedicine. The shapes of gold nanoparticles could modulate tumor cell behavior. Spherical (AuNPsp), stars (AuNPst) and rods (AuNPr) shapes of polyethylene glycol coated-gold nanoparticles (AuNPs-PEG) were synthesized. Metabolic activity, cellular proliferation, and reactive oxygen species (ROS) were measured and the impact of AuNPs-PEG in metabolic enzymes function was evaluated by RT-qPCR in PC3, DU145, and LNCaP prostate cancer cells. All AuNPs were internalized, and the different morphologies of AuNPs showed to be an essential modulator of metabolic activity. For PC3 and DU145, the metabolic activity of AuNPs was found to rank in the following order from lowest to highest: AuNPsp-PEG, AuNPst-PEG, and AuNPr-PEG. Regarding LNCaP cells, the AuNPst-PEG were less toxic, followed by AuNPsp-PEG and AuNPr-PEG, but it seems not to be dose-dependent. The proliferation was lower in AuNPr-PEG in PC3 and DU145 cells but was stimulated around 10% in most conditions (0.001–0.1 mM) in LNCaP cells (not statistically significant). For 1 mM, LNCaP cells showed a significant decrease in proliferation only for AuNPr-PEG. The outcomes of the current study demonstrated that different AuNPs conformations influence cell behavior, and the correct size and shape must be chosen considering its final application in the field of nanomedicine.